2022
DOI: 10.1029/2021jc017506
|View full text |Cite
|
Sign up to set email alerts
|

Sources of the Levantine Intermediate Water in Winter 2019

Abstract: The Mediterranean Sea is often considered as a miniature ocean for climatic studies (Béthoux et al., 1999;Durrieu de Madron et al., 2011;Tsimplis et al., 2006). Its semi-enclosed geometry fosters a zonal overturning circulation that connects remote areas of the easternmost Levantine Sea with the North Atlantic Ocean, in compensation for the evaporation excess over the basin (Hopkins, 1978). This open thermohaline cell sets the stratification of the whole Mediterranean Sea according to a two-layer flow (Wüst, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Therefore, we wish to emphasize the fact that, unlike the rest of the Mediterranean, the surface layer (consisting of waters of Atlantic origin) and the intermediate layer (formed by waters from the Levantine part of the Mediterranean) move strictly in phase with each other in the Ionian Sea. These results are significant because they not only justify the commonly used two-layer approximation for describing Ionian dynamics [1,[15][16][17][18]39], but also provide insight into the relationships between changes in the Ionian dynamics and hydrographic and bio-geo-chemical properties of the Adriatic and Eastern Mediterranean [1][2][3]11,[22][23][24]. Specifically focusing on the biology, previous studies have shown that changes in the Ionian circulation can affect connectivity patterns between different Mediterranean ecosystems, thereby modulating Lessepsian migrations in the Adriatic [6].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, we wish to emphasize the fact that, unlike the rest of the Mediterranean, the surface layer (consisting of waters of Atlantic origin) and the intermediate layer (formed by waters from the Levantine part of the Mediterranean) move strictly in phase with each other in the Ionian Sea. These results are significant because they not only justify the commonly used two-layer approximation for describing Ionian dynamics [1,[15][16][17][18]39], but also provide insight into the relationships between changes in the Ionian dynamics and hydrographic and bio-geo-chemical properties of the Adriatic and Eastern Mediterranean [1][2][3]11,[22][23][24]. Specifically focusing on the biology, previous studies have shown that changes in the Ionian circulation can affect connectivity patterns between different Mediterranean ecosystems, thereby modulating Lessepsian migrations in the Adriatic [6].…”
Section: Discussionmentioning
confidence: 67%
“…The above quoted findings, along with the fact that changes in the hydrographic properties of the Adriatic and the Eastern Mediterranean (EMed) are in phase with the Ionian dynamics [1,2,11,[22][23][24], indirectly confirm that the variability of the Ionian surface structure is primarily driven by the deformations of the interface between deep and intermediate waters, but open an interesting theoretical issue concerning the dynamical mechanism that constrains the intermediate and surface layer to move rigidly in phase one with the other.…”
Section: Introductionmentioning
confidence: 74%
“…This implies that, unlike the rest of the Mediterranean, in the Ionian Sea the surface layer, consisting of Modified Atlantic Water, and the intermediate layer, formed by Levantine Intermediate Waters, over time-scales longer than one year, move strictly in phase with each other. These results are significant because they not only support the commonly used two-layer approximation for describing the Ionian dynamics [1,[15][16][17][18]39] but also provide valuable insights into the relationships between changes in the Ionian dynamics and the hydrographic and bio-geo-chemical properties of the Adriatic and Eastern Mediterranean [1][2][3]11,[22][23][24]. Specifically focusing on the biology, previous studies have shown that changes in the Ionian circulation can affect connectivity patterns between different Mediterranean ecosystems, thereby modulating Lessepsian migrations in the Adriatic [6].…”
Section: Discussionmentioning
confidence: 84%
“…The above quoted findings, along with the fact that changes in the hydrographic properties of the Adriatic and the Eastern Mediterranean (EMed) are in phase with the Ionian dynamics [1,2,11,[22][23][24], indirectly confirm that the variability of the Ionian sur-face structure is primarily driven by the deformations of the interface between deep and intermediate waters but open an interesting theoretical issue concerning the dynamical mechanism that constrains the intermediate and surface layer to move rigidly in phase one with the other.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence anticyclones are coherent larger vortices, while cyclones in the Mediterranean sea as detected by altimetry are instead cyclonic gyres bounded by topography or hydrographic fronts such as the Ligurian, South-Western Crete or Rhodes gyre (Millot and Taupier-Letage, 2005;Stegner et al, 2021). MLD evolution inside these cyclonic gyres was already surveyed because of their importance for biological production, in particular with the development of BGC-Argo (d'Ortenzio et al, 2021;Taillandier et al, 2022). Apart for specific campaigns, Mediterranean anticyclones remain poorly analyzed despite being more coherent, and statistical comparison based on vertical profiles is lacking, with the noticeable exception of the BOUM campaign surveying 3 anticyclones across the basin in 2008 (Moutin and Prieur, 2012).…”
Section: Introductionmentioning
confidence: 99%